HUBUNGAN KEDISIPLINAN SISWA DENGAN MOTIVASI BELAJAR SISWA KELAS IV SDN 104214 KEDAI DURIAN KECAMATAN DELITUA 2020/2021 - Sri Mardiana; Thessa Herdyana; Mastari Ramadhani (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2021)
The formulation of the problem in this study is the low level of student motivation due to the low level of student discipline. This study aims to determine how big the level of the relationship between student discipline and learning motivation of fourth grade students at State Elementary School 104214 Delitua Academic Year 2020/2021 This research is a correlational study with the number of research subjects as many as 76 students from fourth grade students of State Elementary School 104214 Delitua Academic Year 2020/2021. This research was carried out in two stages, the first stage was a questionnaire trial, then the second stage was the distribution of questionnaires to all samples of class IV at the 104214 Delitua State Elementary School for the 2020/2021 Academic Year. There are two variables in this study, student discipline as the independent variable and student motivation as the dependent variable. Data collection techniques in this study used a questionnaire. The data analysis technique used is the Product Moment Correlation analysis formula, determination and t test. From the calculation results, the level of tendency of the variable x (student discipline) is included in the category of tending to be moderate. While the level of tendency of the variable y (student learning motivation) is included in the category tend to be too. Analysis of the research data shows that there is a relationship between student discipline and student motivation in class IV Elementary School 104214 Delitua Academic Year 2020/2021, it can be seen from the results of the correlation calculation, namely rcount = 0.628 while rtable = 0.225 with dk = n-2 at significance level alpha = 0.05, so rcount > rtable. The coefficient of determination (large relationship) of the two variables is 39.44%. This shows that the low learning motivation of students is influenced by 39.44% of the level of student discipline, the rest is influenced by other factors that are not analyzed. The results of the t-test calculation show that tcount = 8.85 while ttable = 1.99 with dk = n-2 at a significant level of alpha = 0.05, thus the hypothesis that states "there is a relationship between student discipline and student learning motivation in students Grade IV of State Elementary School 104214 Delitua Academic Year 2020/2021” has been verified (Ha is accepted and significant because tcount > ttable).